Spatiotemporal Distributions of Non-ophidian Ophidiomorphs, With Implications for Their Origin, Radiation, and Extinction - Campbell Mekarski, Michelle; Pierce, Stephanie E.; Caldwell, Michael W. (Frontiers in Earth Science, 2019)
Non-ophidian ophidiomorphs, colloquially referred to as ‘dolichosaurs,’ are small-bodied aquatic lizards that lived in shallow seaways, rivers, and reef environments during the Late Cretaceous. Preservational, geographic, and taphonomic biases in this group make trends in biodiversity difficult to assess. This is exemplified by the fact that the majority of the described species are monotypic and known only from single specimens, imparting very little information on morphological or spatial variation. Here we present a revision of the spatial and temporal distributions of non-ophidian ophidiomorph lizards (‘dolichosaurs’) from Cretaceous sediments worldwide. The fossil record of dolichosaurs begins in the Valanginian (Early Cretaceous). The late Early Cretaceous records are sparse but suggest a wide geographic distribution spanning the Tethys and Western Pacific. This is followed by a dense Cenomanian record from Tethyan and British deposits, and rarer specimens from North America. Though there is a substantial drop in the number of specimens recorded from the Turonian-Maastrichtian, these rare occurrences represent the largest geographical distribution of dolichosaurs: spanning Europe, North America, and South America before going extinct during the end-Cretaceous mass extinction. These occurrences indicate that ophidiomorphs most likely originated in the Jurassic Tethys and continued to radiate spatially and phylogenetically until the end of the Mesozoic, showing much more temporally and environmentally diverse patterns than previously indicated.